(untitled) (Indonesian Theological Justice Review, 2024)
Religious non-governmental organizations (NGOs) have long been active in promoting social justice and development in Indonesia, particularly in the areas of poverty alleviation, education, and human rights. This paper examines the role of faith-based NGOs in addressing social inequities and their impact on community development in Indonesia. By analyzing the work of Islamic, Christian, and interfaith NGOs, the study explores how these organizations draw on religious principles to inform their social justice agendas. The paper focuses on key areas such as community empowerment, disaster relief, gender equality, and advocacy for marginalized groups. It also addresses the challenges that faith-based NGOs face, including political interference, interfaith tensions, and resource limitations. The research highlights the unique strengths of religious NGOs, such as their ability to mobilize grassroots support and leverage religious networks to foster social change. The paper concludes that faith-based initiatives play a vital role in Indonesia’s development, but greater coordination and collaboration with secular NGOs and government agencies are necessary to maximize their impact. Recommendations include strengthening partnerships between religious and secular organizations, improving resource distribution, and ensuring that faith-based organizations align their goals with broader human rights frameworks.